A Moral Analysis of Carbon Majors' Role in Climate Change. (1st April 2020) - Grasso, Marco; Vladimirova, Katia
Abstract : Two-thirds of global industrial greenhouse gas emissions over the past two centuries can be traced to the activities of a handful of companies ('carbon majors'). Based on their direct contribution to climate change in terms of carbon emissions and on a number of morally relevant facts, this article proposes a normative framework to establish the responsibilities that carbon majors have in relation to climate change. Then, the analysis articulates these responsibilities in the form of two duties: a duty of decarbonisation and a duty of reparation. The duty of decarbonisation entails a large-scale transformation that carbon majors ought to undergo in order to reduce and eventually eliminate carbon emissions from their entire business model. The duty of reparation implies rectification through disgorgement of funds for the wrongful actions of carbon majors, which resulted in negative climate impacts, starting from the most socially vulnerable groups affected by climate change. Finally, the article indicates possible practical implications of these duties.